PERSEPSI KETUA PENGADILAN NEGERI DAN KETUA PENGADILAN AGAMA TENTANG PENINJAUAN KEMBALI (PK) PASCA PUTUSAN MK NO. 34/PUU-XI/2013 DALAM HUKUM ACARA PERDATA - Bahran Basri (Universitas Islam Negeri Antasari Banjarmasin, 2015)
Since test material to the provisions of Pasal 268 ayat (3) Undang-Undang No. 8 Tahun 1981on Criminal Proceedings in Mahkamah Konstitusi, Mahkahmah decided in its decision number 34 /PUU-XI / 2013, which states that the provisions was inconsistent with the Undang-Undang Dasar1945, so it does not have binding legal force. Therefore, Peninjauan Kembali (PK) in criminal cases maybe done more than once with the new circumstances or conditions found substantial novum new foundduring previous PK undiscovered. If problems associated PK novum criminal case is considered sub-stantial, and neither should Novum issues related PK in civil cases, as may be after the filing of the PKand disconnected, no new circumstances or substantial novum recently discovered that during theprevious PK undiscovered or if there is a decision of a judges mistake or a real mistake was discoveredafter PK decided. PK is an extraordinary remedy that aims to find justice and truth material. Justice cannot be limited by time or formal provision that limits that PK is only one time. Justice is a very basichuman needs, the more basic human needs of the rule of law. But in civil cases, the results of this studyindicate that the filing PK limited only once.